Donald and the fake news! - Metaxas, Eric (Donald the caveman, 2020)
After Donald the Caveman drained the Swamp and built the Wall, everyone was happy! Everyone, that is, except the freedom-haters who called themselves “The Resistance.” Led by an evil sorceress named Madame Miss Speaker, the Resistance tried to contradict everything Donald said to make him seem like a bad leader. These troublemakers even used Fake News to spread the rumor that Donald was working for the Russians! But Donald was not discouraged<U+2014>he knew just what to do. He fought back with the truth. And the truth will always defeat Fake News.